Comparative Study on Biosorption of Zn(II), Cu(II) and Cr(VI) from Textile Dye Effluent Using Sawdust and Neem Leaves Powder - K. Gopalakrishnan; V. Manivannan; T. Jeyadoss (E-Journal of Chemistry)
The performance of the low cost adsorbents such as sawdust and neem leaves powder in removing the heavy metals like Zn(II), Cu(II) and Cr(VI) from textile dye effluent are reported. Adsorbent dosage, pH and contact time were taken as parameters for biosorption study. Removal of heavy metal ions from the textile dye effluent increases with increase in adsorbent dosage. The influence of pH and contact time was maximum for removal of heavy metal ions. The presence of the decreased heavy metal toxicity in the treated textile dye effluent was evaluated through the percentage of seed germination of Vigna mungo L. On comparison, sawdust was found to be good adsorbent compared to neem leaves powder.